FAKTOR YANG MEMPENGARUHI KUALITAS KEBERSIHAN LINGKUNGAN TERHADAP KENYAMANAN PASIEN RAWAT JALAN DI PUSKESMAS KARANG TALIWANG KOTA MATARAM TAHUN 2024 - Muh. Sahiril; Slamet Mardiyanto Rahayu; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Fathurrahman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
Patient perceptions about the quality of environmental cleanliness of the Community Health Center who felt that Environmental Cleanliness was in the good category were 81 people (83.5%), Patient perceptions about environmental cleanliness of the Community Health Center who felt that Environmental Cleanliness was sufficient were 16 people (16.5%). Patients who felt comfortable with the environmental conditions of the Karang Taliwang Community Health Center were 79 people (81.4%). The number of patients who felt uncomfortable with the environmental conditions of the Karang Taliwang Community Health Center was 18 people (18.6%). Based on the results of statistical tests obtained a p value (Asymptotic Significance) Pearson Chi Square = 0.037 <α 0.05 (Significant) which there is a significant relationship between environmental cleanliness quality factors and the comfort of outpatients at the Karang Taliwang Community Health Center. This means that environmental cleanliness quality factors will affect patient comfort, the better the quality of environmental cleanliness of the Community Health Center, the more comfortable the patient feels.